Identifying the drivers and constraints to adoption of IPM among arable farmers in the UK and Ireland. Issue 9 (15th May 2021) - Creissen, Henry E; Jones, Philip J; Tranter, Richard B; Girling, Robbie D; Jess, Stephen; Burnett, Fiona J; Gaffney, Michael; Thorne, Fiona S; Kildea, Steven
Abstract: BACKGROUND: Arable crops in temperate climatic regions such as the UK and Ireland are subject to a multitude of pests (weeds, diseases and vertebrate/invertebrate pests) that can negatively impact productivity if not properly managed. Integrated pest management (IPM) is widely promoted as a sustainable approach to pest management, yet there are few recent studies assessing adoption levels and factors influencing this in arable cropping systems in the UK and Ireland. This study used an extensive farmer survey to address both these issues. RESULTS: Adoption levels of various IPM practices varied across the sample depending on a range of factors relating to both farm and farmer characteristics. Positive relationships were observed between IPM adoption and farmed area, and familiarity with IPM. Choice of pest control information sources was also found to be influential on farmer familiarity with IPM, with those who were proactive in seeking information from impartial sources being more engaged and reporting higher levels of adoption. CONCLUSION: Policies that encourage farmers to greater levels of engagement with their pest management issues and more proactive information seeking, such as through advisory professionals, more experienced peers through crop walks, open days and discussion groups should be strongly encouraged. Abstract : By encouraging farmers to actively engage with informed, impartial professionals and peers we are likely to increase adoption of IPM practices paving the way for more sustainable crop production systems. © 2021 The Authors. Pest Management Science published by John Wiley & Sons Ltd on behalf of Society of Chemical Industry.